1999
DOI: 10.1515/znc-1999-3-420
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Studies on Association of Human Translation Initiation Factor eIF4E with mRNA cap-Analogues

Abstract: Binding of a long series of mono- and dinucleotide analogues of the 7-methylguanosine containing 5′-mRNA-cap to human protein translation initiation factor eIF4E has been investigated by means of fluorescence. A new methodological approach in gathering and analysis of the fluorescence data provided us with very accurate values of the association equilibrium constant K and normalized, maximal quenching of the protein fluorescence ΔFmax, during titration of eIF4E by various cap-analogues. The results confirm par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 0 publications
3
14
1
Order By: Relevance
“…This is in contrast to the published data, 12,13) where the binding preference of m 7 GTP over m 7 GpppA/G was observed. The reasons for the discrepancies between these re- sults and ours are not known at present.…”
Section: Resultscontrasting
confidence: 99%
“…This is in contrast to the published data, 12,13) where the binding preference of m 7 GTP over m 7 GpppA/G was observed. The reasons for the discrepancies between these re- sults and ours are not known at present.…”
Section: Resultscontrasting
confidence: 99%
“…From a set of three independent measurements the average K d was found to be 10 (±3) nM for 7MeGTP, which is nearly identical to the value (9.1 nM) previously reported for eIF4E purified by cap-affinity chromatography [25]. The K d value is almost 2-orders of magnitude lower than that reported by others [26,29,30], The fluorescence quenching measurements were also conducted with 7MeGDP, 7MeGMP and 7BnGMP under similar condition and the corresponding K d values were found to be 45 (±10) nM, 10,000(±500) nM and 800 (± 200) nm, respectively. Similar trends in the K d values for 7MeGDP (49 nM) and 7MeGMP (1240 nM) were reported by Stolarski's and co-workers [25] Although a Kd value determined by fluorescence titration has not been reported for 7BnGMP, a nearly 9-fold greater K d value (7,000 nM) was recently determined for 7BnGMP by a novel mass spectroscopic technique [47].…”
Section: Fluorescence Quenching Cap-analog Binding Studiessupporting
confidence: 85%
“…However, extensive dialysis may alter the functional integrity of eIF4E [24,25]. K d values for eIF4E with the cap analogue 7MeGTP have been reported over a broad range from 10 −5 to 10 −8 M −1 [22,23,[25][26][27][28][29][30]. Recently, Stolarski and co-workers have shown that even after repeated dialysis or anion exchange chromatography, 60% of the resulting recombinant eIF4E can still be bound to cap-analogues used for elution [25].…”
Section: Introductionmentioning
confidence: 99%
“…U1 snRNA, which harbors a trimethylated cap in the cytoplasm, did not detectably coimmunoprecipitate with eIF4E (Fig. 6D), as was evident from several observations: (1) Cellular U snRNPs appear to be largely free of sequestering CBPs, based on their quantitative IP using anti-trimethyl G (Bringmann et al 1983); (2) eIF4E binds trimethylated caps 10-fold less efficiently than it binds monomethylated caps (Wieczorek et al 1999); and (3) snurportin binds the trimethylated cap of cytoplasmic U snRNAs (Will and Lü hrmann 2001) so as to mediate together with IMPb snRNA import into nuclei to function in pre-mRNA splicing (Rollenhagen and Pante 2006;Cook et al 2007).…”
Section: Resultsmentioning
confidence: 68%